A dual transcriptome analysis reveals accession-specific resistance responses in Lathyrus sativus against Erysiphe pisi - Maravilha, Rita M.; Fernandes, Telma; Barros, Pedro M.; Leitão, Susana T.; Rubiales, Diego; Vaz Patto, Maria Carlota; Santos, Carmen (Frontiers in Plant Science, 2025)
Lathyrus sativus (grass pea) is a valuable crop for sustainable agriculture, offering dietary benefits and desirable agronomic traits. However, its yield stability is limited by diseases such as powdery mildew caused by Erysiphe pisi. Increasing fungal resistance to pesticides and environmental concerns demand the development of resistant crop varieties. To identify key defense mechanisms and effector genes involved in the Lathyrus sativus-Erysiphe pisi interaction we analyzed four L. sativus accessions exhibiting varying resistance to E. pisi (resistant, partially resistant, partially susceptible, and susceptible) using a dual RNA-Seq experiment across different time points. We observed a host biphasic response, characterized by an initial burst of gene expression, followed by a quiescent phase, and a subsequent wave of intense gene expression. Common L. sativus defense mechanisms included antifungal protein expression, cell wall reinforcement, and reactive oxygen species-mediated defense. These defenses involved respectively Bowman-Birk type proteinase inhibitors, peptidyl-prolyl cis-trans isomerases and mannitol dehydrogenases. The resistant accession specifically activated early reinforcement of structural barriers associated with lignin biosynthesis and the phenylpropanoid pathway, along with sustained chemical defenses (e.g. eugenol synthase 1), epigenetic regulation, and oxidative stress responses thorough peroxidases and heat shock proteins. The partial resistant accession exhibited a front-loaded defense response at early infection stages. Contrastingly, the partially susceptible accession exhibited a weaker baseline defense, with a slower and less robust response targeting pathogen infection. We identified potential E. pisi effectors, including genes involved in cell wall hydrolysis (e.g. mannosidase DCW1), nutrient acquisition (e.g. secreted alpha-glucosidase), and virulence (e.g. SnodProt1), with a higher diversity of effectors identified in the susceptible accession. In conclusion, this study identifies novel targets such as NLRs and effectors, antifungal proteins and genes related to cell wall reinforcement, within the complex Lathyrus sativus-Erysiphe pisi interaction to support future breeding programs aimed at enhancing resistance to E. pisi in L. sativus and related species.